The Influence Work Environment, Job Satisfaction and Work Stress on Turnover Intention - Kusuma, Nanda Perdi; Septyarini, Epsilandri; Kusuma, Nala Tri (Universitas Muhammadiyah Makassar, 2025)
This study investigates the influence of work environment, job satisfaction, and job stress on turnover intention among employees at DM Baru Retailindo, Bantul. The research adopts a quantitative design, involving the entire employee population as the sample, totaling 49 respondents, selected using a saturated sampling technique. Data collection was conducted through structured questionnaires, and the responses were analyzed using multiple statistical methods to assess both partial and simultaneous effects of the independent variables on turnover intention. The findings indicate that the work environment exerts a positive and significant effect on turnover intention, suggesting that certain aspects of the workplace may contribute to employees’ desire to leave. Conversely, job satisfaction demonstrates a negative and significant effect, meaning that higher levels of satisfaction are associated with lower turnover intention. Additionally, job stress shows a positive and significant influence, implying that increased stress levels elevate the likelihood of employees intending to resign. The simultaneous analysis confirms that the three factors collectively have a significant impact on turnover intention. These results hold important practical implications for human resource management at DM Baru Retailindo. Efforts to improve the physical and social aspects of the work environment, enhance job satisfaction through recognition and career development, and mitigate job stress through workload management could contribute to lowering turnover rates. The study provides valuable insights for managerial decision-making and may serve as a reference for future research aimed at strengthening employee retention strategies and ensuring organizational sustainability.